Preliminary Results of Double Difference Tomography at Sunda-Banda Arc. Issue 1 (October 2021) - Haolia,; Sulaiman, M. I.; Brilianti, P. T.; Nugroho, R. P.; Madrinovella, I.; Abdullah, A.; Zaky, D. A.; Suhardja, S. K.; Priyono, A.; Widiyantoro, S.; Ramdhan, M.; Nugraha, A. M. S.
Abstract: The Sunda-Arc transition to the Banda Arc is located on the south of the Flores Island, Indonesia, where the Australian lithosphere is moving to the north direction. On-going subduction process dictates the tectonic setting though some studies also suggest a collision and obduction may occur in the past due to of plate buoyancy. This area has active seismicity with frequent large magnitude events. To better understand the tectonic system in this region, we performed double-difference tomography inversion using regional events. We obtained the data catalog from the Indonesian Agency of Meteorology, Climatology, and Geophysics ranging from 116° to 125° east longitude and -6.5° to 12.5° latitude. We collected 4312 events data, detected from 15 stations from January 2015 to December 2019. Final relocated hypocenters showed a reduced fixed-depth problem and a more clustered event, although some deep events disappear. Most events are related to the subducting Benioff zone with some clustered events in the northern area may be related to back-arc thrust. We also observed clustered events near active volcano region and reduced shallow seismicity region to the west of the Timor Island. Resolution test using the checkerboard and Derivative weigh Sum (DWS) shows that fair P wave resolution can be achieved until 300 km, although a smearing start to show at a deeper depth. However, due to lack of arrival S wave data, the resolution test suggest good resolution can only be seen until a depth of 100 km. Tomogram P and S wave models show a clear dipping subducting slab from south to North down to a 250 km. We also spot a fast velocity band near the Timor Island area that similar to the previous tomography study, interpreted as sliver forearm. We spotted a band of lower Vp, lower Vs and higher Vp/Vs at shallow depth close to the volcanic line and we interpreted this as a zone of higher temperature, that may relate to magmatic activity in this region. We also noticed a zone of low velocity and higher Vp/Vs that may relate with dehydration and partial melting. However, we feel this still uncertain due to low Vs resolution.